Association Between Single-Nucleotide Polymorphisms in HLA Alleles and Human Immunodeficiency Virus Type 1 Viral Load in Demographically Diverse, Antiretroviral Therapy–Naive Participants From the Strategic Timing of AntiRetroviral Treatment Trial. (13th June 2019) - Ekenberg, Christina; Tang, Man-Hung; Zucco, Adrian G; Murray, Daniel D; MacPherson, Cameron Ross; Hu, Xiaojun; Sherman, Brad T; Losso, Marcelo H; Wood, Robin; Paredes, Roger; Molina, Jean-Michel; Helleberg, Marie; et al.
Abstract: The impact of variation in host genetics on replication of human immunodeficiency virus type 1 (HIV-1) in demographically diverse populations remains uncertain. In the current study, we performed a genome-wide screen for associations of single-nucleotide polymorphisms (SNPs) to viral load (VL) in antiretroviral therapy–naive participants (n = 2440) with varying demographics from the Strategic Timing of AntiRetroviral Treatment (START) trial. Associations were assessed using genotypic data generated by a customized SNP array, imputed HLA alleles, and multiple linear regression. Genome-wide significant associations between SNPs and VL were observed in the major histocompatibility complex class I region (MHC I), with effect sizes ranging between 0.14 and 0.39 log10 VL (copies/mL). Supporting the SNP findings, we identified several HLA alleles significantly associated with VL, extending prior observations that the (MHC I) is a major host determinant of HIV-1 control with shared genetic variants across diverse populations and underscoring the limitations of genome-wide association studies as being merely a screening tool. Abstract : "To investigate the impact of host genetics on human immunodeficiency virus type 1 control among individuals of different ancestry, we performed genome-wide association screening and HLA imputation in a demographically diverse, antiretroviral therapy–naive cohort".